Librarian-Faculty Collaboration in Information Literacy Instruction: Experiences from the University of Jos Law Library - Lawal, Vicki; Opara, Subrina O. (MiddleBelt Journal of Library and Information Science, 2020)
Information Literacy in various disciplines have served as a means of promoting critical learning and problem solving skills in the use of a variety of information sources for research. Collaboration between librarians and faculty is very important if success is to be achieved in implementing Information Literacy programmes. This paper presents preliminary findings on the execution of a web-based Information Literacy tutorial at the University of Jos Law Library. It seeks to explore the implications of sustained partnership in Information Literacy instruction as a key aspect of legal education in the institution.